Progress of RAGE Molecular Imaging in Alzheimer’s Disease - Kong, Yanyan; Liu, Cuiping; Zhou, Yinping; Qi, Jingxuan; Zhang, Chencheng; Sun, Bomin; Wang, Jiao; Guan, Yihui (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease, characterized by senile plaques (SPs) caused by amyloid beta (Aβ) deposition and neurofibrillary tangles (NFTs) of abnormal hyperphosphorylated tau protein. RAGE is a receptor of advanced glycation end-products (AGEs), which are deposited during vascular dysfunction. It may cause AD by binding Aβ and releasing reactive oxygen species (ROS), which further exacerbates Aβ deposition and eventually leads to SPs and NFTs. As it is involved in early AD, RAGE has the potential to be a more potent biomarker compared to Aβ. While positron emission tomography (PET) provides a way to detect valuable information about the underlying pathological processes many years before the appearance of clinical symptoms, a tracer that targets RAGE is needed to further reveal the role of RAGE in AD pathology and for the early diagnosis of AD. In this review, we have introduced a RAGE-targeting probe called [18F]-FPS-ZM1. With probes targeting Aβ and tau protein, the role of [18F]-FPS-ZM1 in exploring the pathogenesis of RAGE in AD was verified. Due to its high specificity and affinity for RAGE, [18F]-FPS-ZM1 is believed to provide accurate and reliable in vivo data for studying local or whole brain pathological changes. Thus, [18F]-FPS-ZM1 could greatly promote the early diagnosis and evaluation of AD and provide a way to reflect the early pathological mechanism of AD.